Effect of Integrated Nitrogen, Phosphorus, and Farmyard Manure on Post-Harvest Quality and Storability of Onion (Allium Cepa L.) - Tekeste, Negasi; Dechassa, Nigussie; Woldetsadik, Kebede; Dessalegne, Lemma; Takele, Abuhay (Journal of Postharvest Technology, 2017)
A series of laboratory experiments were conducted during the 2011 and 2012 growing season under irrigation using 12 treatment combinations of NP and FYM at Melkassa Research Centre in the Central Rift Valley Region of Ethiopia. The objective of the experiment was  to investigate the effect of integrated NP and FYM use on postharvest quality and shelf life of Bombay red onion bulbs. The experiment was  laid out as a randomized complete block design with three replications per treatment in the store. Results of the study revealed that combined  application of fertilizer at 51.75 kg N+ 69 kg P2O5 + 5 t FYM ha-1resulted in minimum physiological weight loss of bulbs throughout the whole  storage period. Sprouting was lowest in bulbs treated with 51.75 kg N+ 69 kg P2O5 + 5 t FYM ha-1 while it was highest at 138 kg N+ 184  P2O5kg+40 t FYM ha-1. Application of 34.5 kg N+ 46 kg P2O5 + 10 t FYM ha-1led to minimum bulb rotting. Total soluble solids(TSS) and  percent dry matter recorded maximum with application of 51.75 kg N+ 69 kg P2O5 + 5 t FYM ha-1. Pyruvate content of onion bulbs showed an  increasing trend with increasing rates of fertilizer combinations, where treatment having 138 kg N+ 184 P2O5 kg+ 40 t FYM ha-1recorded the  highest. Highest marketability was recorded in bulbs treated with 86.25 kg N+115 kg P2O5+25 t FYM ha-1fertilizer combinations. Marketability  of bulbs dropped to about 85% after six weeks and 40% after 12 weeks of storage while the best treatment recorded 94% and 61.5% at  respective storage periods. From results of the study, integrated application of 69 kg N+ 92 kg P2O5 + 20 t FYM ha-1can be a good  compromise for postharvest quality and shelf life of Bombay Red onion bulbs in the central Rift Valley region of Ethiopia.
Keywords: Farmyard manure; inorganic N P; onion; shelf life; quality